Nutritional status and various morbidities among school children of a coastal area in South India - Abraham, Sherin Billy; Chauhan, Ramesh Chand; Rajesh, Muthu; Purty, Anil Jacob; Singh, Zile (International Journal of Research in Medical Sciences, 2017)
Background: Malnutrition and poor health among school children is the common cause of low school enrolment, high absenteeism, early dropout and poor classroom performance. This study was conducted to assess the various morbidities and nutritional status among school children. Methods: This descriptive study was conducted during year 2013 in a higher secondary school located in a coastal area of Puducherry. A total of 714 students were interviewed and examined. A pre-designed and pre-tested questionnaire was used to interview and examine all the participated students. Body weight and height were measured using standardized procedures. WHO criteria for classification of nutritional status was used. Visual acuity and colour vision was assessed using Snellen’s chart and Ishihara’s pseudo isochromatic chart respectively. Mean scores and proportions were calculated and chi-square test was applied. P value of <0.05 was considered as statistically significant. Results: Among 714 student, 369 (51.4%) were males and 345 (48.6%) were females. The mean age of children was 10.2 ± 3.1 years. Among all age groups and both sexes, the observed BMI was lower as compared to the reference values. The prevalence of underweight among children of 5-9 years was (30.7%) and (1.1%) were severely underweight. The prevalence of stunting was 10.4%, including 0.1% of severely stunted children. A total of 30.7% children were thin (low BMI for age). Pallor (39.5%), myopia (34.9%) and dental caries (14.7%) were the common morbidities observed among children. The pallor was observed more commonly among girls and this difference was statistically significant (p value <0.05). Conclusion: Under-nutrition is a prevalent condition among school children. Apart from various nutritional programmes, health education to parents, community and school teachers are quite important to address this problem.